2017
DOI: 10.1080/07011784.2017.1394801
|View full text |Cite
|
Sign up to set email alerts
|

Benefits and limitations of using isotope-derived groundwater travel times and major ion chemistry to validate a regional groundwater flow model: example from the Centre-du-Québec region, Canada

Abstract: Understanding groundwater dynamics at the regional scale (> 100 km) is essential to the development of sustainable water management regulations. Groundwater flow models are increasingly used to support these strategies. However, in order to be reliable, these models need to be calibrated and validated. The objective of this work is to evaluate the benefits and the limitations of using isotope-derived groundwater travel times and major ion chemistry to validate a regional-scale groundwater flow model in the hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 66 publications
0
21
0
Order By: Relevance
“…They found that only a weighted multivariate objective function of H, Q GW , and TT could properly calibrate the karst conduit network and hydraulic parameters and that sequential calibration with single‐variable objective functions did not result in adequate models. Gagné et al () compared the manual calibration of a large, basin‐scale GW flow model to automated calibration based on a weighted multivariate objective function, including both observations of H and Q base . The performance of the two calibration approaches was assessed by comparing simulated to measured H, Q base , and RT (derived from measurements of C).…”
Section: Review Of the Use Of Unconventional Observation Typesmentioning
confidence: 99%
See 2 more Smart Citations
“…They found that only a weighted multivariate objective function of H, Q GW , and TT could properly calibrate the karst conduit network and hydraulic parameters and that sequential calibration with single‐variable objective functions did not result in adequate models. Gagné et al () compared the manual calibration of a large, basin‐scale GW flow model to automated calibration based on a weighted multivariate objective function, including both observations of H and Q base . The performance of the two calibration approaches was assessed by comparing simulated to measured H, Q base , and RT (derived from measurements of C).…”
Section: Review Of the Use Of Unconventional Observation Typesmentioning
confidence: 99%
“…Automated calibration based on a weighted multivariate objective function reduced the mismatch between observed and simulated RT by more than half compared to manual calibration. Gagné et al () demonstrated that GW RTs may be reproduced with a model calibrated against observations of H and Q base , but only if that model is calibrated based on automated inversion of a weighted multivariate objective function—manual calibration failed in finding a parameter set to reproduce observations beyond the ones directly used in the calibration data set.…”
Section: Review Of the Use Of Unconventional Observation Typesmentioning
confidence: 99%
See 1 more Smart Citation
“…The papers focus on three main components of aquifer characterization, i.e. aquifer geometry (Légaré-Couture et al 2018;Nadeau et al 2018;Walter et al 2018), hydrogeochemistry and isotope tracers (Chaillou et al 2018;Rey et al 2018;Beaudry et al 2018), and groundwater flow modeling and particle tracking (Gagné et al 2018;Janos et al 2018;Montcoudiol et al 2018;Turgeon et al 2018). The paper by Walter et al (2018) combines the topics of geometry and hydrogeochemistry.…”
mentioning
confidence: 99%
“…The results were used to build a regional-scale conceptual model which describes recharge, evaporation, mixing and discharge processes. Gagné et al (2018) present a 3D model of groundwater flow for the Bécancour and Nicolet watersheds in the Centre-du-Québec region (BEC and NSF). In this region, the main aquifer is located in the sedimentary fractured bedrock and is overlain by till, sand and clay from the Champlain Sea.…”
mentioning
confidence: 99%